2009
DOI: 10.1007/s12237-009-9140-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Dissolved Trace Metals in Jamaica Bay, NY: Importance of Wastewater Input and Submarine Groundwater Discharge in an Urban Estuary

Abstract: Jamaica Bay, NY, is a highly urbanized estuary within the boroughs of New York City conspicuously lacking published information on dissolved trace metal concentrations. The current study examines the distribution and cycling of trace metals in that embayment with data gathered during cruises in November 2004, April 2005, and June 2006. Most of the metal distributions (Fe, Zn, Co, Ag, Cu, Pb, Ni) in the water column are explained by the input of substantial volumes of treated wastewater effluent. However, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…Santos et al [2011a], using rapid (90 min) sampling of a STE over a 16 h period, provided evidence that tide-induced water exchange was a control on U removal (and release in the case of Ba). Beck et al [2009] found that Cu was removed within the STE of a coastal New York embayment, though they did not comment on the potential driving mechanism for this process. Regardless, the time-scale over which these conditions that are a removal will determine whether or not STEs are important for trace metal removal on longer (e.g., decadal to centennial and beyond) time scales [Beck et al, 2010].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Santos et al [2011a], using rapid (90 min) sampling of a STE over a 16 h period, provided evidence that tide-induced water exchange was a control on U removal (and release in the case of Ba). Beck et al [2009] found that Cu was removed within the STE of a coastal New York embayment, though they did not comment on the potential driving mechanism for this process. Regardless, the time-scale over which these conditions that are a removal will determine whether or not STEs are important for trace metal removal on longer (e.g., decadal to centennial and beyond) time scales [Beck et al, 2010].…”
mentioning
confidence: 99%
“…Trezzi et al [2016] reported on SGD in a Mediterranean region where mine tailings had accumulated along the shoreline for several decades. They found that zinc (Zn) and lead (Pb) fluxes were significantly elevated in SGD relative to other locations worldwide [e.g., Beck et al, 2009]. Again, the mobilization of these metals in groundwater was attributed to the Fe and Mn redox cycles and the suspected low pH of the groundwater as it passed through the sediment deposits left behind from mining activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity at 30 cm was equal to 4. Beck et al (2010) observed similar concentration change of Pb for the SGD impacted site in Great South Bay, NY, at the end of Roe Avenue in the town of Patchogue, USA caused by enriched Pb concentrations in groundwater (Beck et al, 2009). Investigations on dissolved trace metals launched in Jamaica Bay, NY, USA indicated similar patterns for Zn and Co in the groundwater impacted site and provide evidence for trace metal input due to SGD (Beck et al, 2009).…”
Section: Trace Metals Pore Water Profiles In the Bay Of Puckmentioning
confidence: 75%
“…Zoriy et al analysed the distribution of Pt in kidney slices of cisplatin-exposed mice by LA-ICP-SFMS. 89 They found differential patterns of 196 Pt + , 63 Cu + and 64 Zn + with a clear enrichment of platinum in the medullar region.…”
Section: Biological and Environmental Samplesmentioning
confidence: 97%